2022
DOI: 10.1002/smi.3134
|View full text |Cite
|
Sign up to set email alerts
|

Losing sleep over work: A self‐determination theory view on need frustration, sleep disturbance, and mental ill health

Abstract: Given the centrality of sleep and work in most individuals' lives, it is interesting to note that an empirical understanding of the association between what happens in the workplace and how well people sleep is in an early stage of development, at least relative to other topics that are of interest in the literature on stress and health. Using self-determination theory, the current study examined how maladaptive motivational processes at work relate to sleep disturbance and mental ill health. In line with hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 83 publications
(151 reference statements)
0
6
0
Order By: Relevance
“…Further to this, present findings reveal that new career starters seek relatedness and belonging in social activities explored while procrastinating bedtime, often through social media and niche interests. Research suggests that frustration of basic psychological needs being met is positively correlated with sleep disturbance (Niemiec et al, 2022): it may be that bedtime procrastination is one mediator of this relationship. Activities sought out during me‐time before bed may also serve as coping mechanisms for negative affect and feelings.…”
Section: Discussionmentioning
confidence: 99%
“…Further to this, present findings reveal that new career starters seek relatedness and belonging in social activities explored while procrastinating bedtime, often through social media and niche interests. Research suggests that frustration of basic psychological needs being met is positively correlated with sleep disturbance (Niemiec et al, 2022): it may be that bedtime procrastination is one mediator of this relationship. Activities sought out during me‐time before bed may also serve as coping mechanisms for negative affect and feelings.…”
Section: Discussionmentioning
confidence: 99%
“…(2002). In addition, the three needs were parcelled for satisfaction and frustration, respectively, as previously done in SDT research (Halvari et al., 2017; Niemiec et al., 2022). For the variables perceived controlling leadership and motivational regulations items were used non‐parcelled.…”
Section: Methodsmentioning
confidence: 99%
“…That is, we randomly assigned items for perceived autonomy-supportive leadership, work engagement, work performance and somatic symptom burden into three parcels, each with two to three items as recommended by Little et al (2002). In addition, the three needs were parcelled for satisfaction and frustration, respectively, as previously done in SDT research (Halvari et al, 2017;Niemiec et al, 2022). For the variables perceived controlling leadership and motivational regulations items were used non-parcelled.…”
Section: Ethical Considerationsmentioning
confidence: 99%
“…In a meta-analysis of randomized clinical trials, it was possible to identify signi cant albeit small effects for physical activity, sedentary behavior, diet, alcohol consumption and smoking cessation (49). Another study, developed in Norway, examined, based on Self-Determination Theory, how maladaptive motivational processes at work are related to sleep disorders and mental health problems (50). The ndings indicated that participants were more likely to report sleep disturbances, anxiety, and depressive symptoms when feeling frustrated in relation to basic psychological needs for autonomy, competence, and relatedness in the workplace (50).…”
Section: Assessmentsmentioning
confidence: 99%
“…Another study, developed in Norway, examined, based on Self-Determination Theory, how maladaptive motivational processes at work are related to sleep disorders and mental health problems (50). The ndings indicated that participants were more likely to report sleep disturbances, anxiety, and depressive symptoms when feeling frustrated in relation to basic psychological needs for autonomy, competence, and relatedness in the workplace (50). In other words, the stronger the psychological needs for a given behavior, the more robust the self-determined motivation to perform it.…”
Section: Assessmentsmentioning
confidence: 99%